Stress Heterogeneity Leading to Void Nucleation within Spherulites for Semi-Crystalline Polymers - Lucien Laiarinandrasana (Crystals, 2019)
Linking the microstructure to the mechanical properties is a key feature in the design and assessment of the durability of semi-crystalline polymers. This paper addresses the importance of a particular architecture inside spherulites. The use of the theoretical tools of continuum mechanics has been combined with experimental observations of the deformation of the microstructure. Microstructural heterogeneities at various scales induced critical regions in the spherulite where voiding has been reported. The local stress state has been investigated using a Finite Element code. A simple Hooke’s law was used for meshes accounting for the alternating crystalline and amorphous lamellae. This allowed a better understanding of the loci of void nucleation in the equatorial region, as well as in the “polar fans”, and were explained by using a criterion based on stress equi-triaxiality.